Physical activity interventions for adolescent suicide ideation and behavior: a rapid review - Bailey, Richard Peter; Samsudin, Nadia; Ries, Francis; Fernandez, Janet Ann (Intelektual Pustaka Media Utama, 2025)
Physical inactivity, sedentary behavior, and mental health issues have become significant public health challenges. This review aimed to investigate the relationship between physical activity, sedentary behavior, and the risk of suicidal ideation and behaviors during adolescence. A systematic review was conducted following PRISMA guidelines. Studies were sourced from SPORTDiscus, Psychology & Behavioral Sciences Collection, and Google Scholar. The review included English-language peer reviewed articles published between January 2018 and March 2023, focusing on physical activity, sport, and mental health in adolescents aged 10 to 19. Adolescents with low levels of physical activity or high levels of sedentary behavior were at greater risk of suicidal thoughts compared to their more physically active counterparts. Although moderate-to-vigorous physical activity was not directly associated with self-harm or mental health disorders, the overall mental health benefits of physical activity, especially in the context of socially engaging sports, were evident. Some aspects of these associations warrant further investigation. Physical activity and sport offer cost-effective, widely accepted interventions that have significant potential to reduce the risk of suicidal ideation and behaviors among adolescents. Given the devastating impact of suicide on young people, incorporating physical activity into mental health promotion and intervention strategies is crucial.